Content Analysis of @fadiljaidi's Instagram as a Reference to Gen Z's Followers Self-existence - Naufal, Syifa Alvernia; Manalu, Margareta (UI Scholars Hub, 2025)
Social media has become the primary platform for generation Z to express themselves and establish their existence in the digital space One of the most influential social media platforms for generation Z is Instagram. Among the many Instagram influencers in Indonesia, Fadil Jaidi stands out for capturing his followers attention through humorous and relatable content. This study aims to analyze how the Instagram content of @fadiljaidi serves as a reference for self-existence among generation Z followers. Using a descriptive qualitative method, data were collected through in-depth interviews with five informants from generation Z who actively follow the Instagram account @fadiljaidi. The study’s results indicate that the main appeal of Fadil Jaidi’s content lies in elements of humor, family closeness, and an authentic and relatable communication style. Beyond entertainment, this content also positively impatcs followers by enhancing self-confidence, social interaction, and digital identity formation. These findings support the theory of self-existense, which encompasses perception, recognition values, freedom, and responsibility in building identity in the digital world. Thus, this study reinforces that social media, particulary Instagram, plays a significant role as a medium for self-existence and social identity formation for generation Z in an ever-volving digital era.